Dental complications of herpes zoster: Two case reports and review of literature - Swati Gupta; V Sreenivasan; Prashant B Patil (Wolters Kluwer Medknow Publications, 2015)
Herpes zoster (HZ) (shingles) results due to reactivation of varicella-zoster virus. Unusual dental complications like osteonecrosis, exfoliation of teeth, periodontitis, and calcified and devitalized pulps, periapical lesions, and resorption of roots as well as developmental anomalies such as irregular short roots and missing teeth may arise secondary to involvement of 2 nd or 3 rd division of trigeminal nerve by HZ. Such cases pose both a diagnostic as well as a therapeutic challenge. We report two such rare dental complications of HZ-spontaneous tooth exfoliation and osteonecrosis of the maxilla in a 70-year-old female patient; and multiple periapical pathoses affecting right half of the mandibular teeth in a 45-year-old female patient. Both the patients did not have any associated systemic illness. The aim of this paper was to compare the present cases with all the 46 cases of osteonecrosis and 6 cases of multiple periapical pathoses secondary to trigeminal zoster reported in literature till date The article also throws light that the occurrence of such dental complications of HZ is not entirely dependent on the immune status of the host.